Comparison of Pointing Throwing Techniques with Standing and Squatting Styles in Pétanque at Hamzanwadi Club - Hary Septianwari; Mahfuz Mahfuz; Karnodinata Karnodinata; Rina Nopiana; Hariadi Hariadi; Suryansah Suryansah (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The research problem lies in the lack of understanding about comparing pointing throwing techniques with standing and squatting styles in the game of petanque at the Hamzanwadi Club. This study explores and analyzes the differences between pitching throwing techniques and standing and squatting styles in the game of petanque at the Hamzanwadi Club. Materials and methods. The study utilizes a descriptive research methodology, employing a quantitative approach to gather and analyze data. The research design is non-experimental, focusing on observing and describing phenomena without manipulating variables. Results. The research results indicate a significant difference. This is because the critical value in the t-table is 2.571, while the obtained t-value is 3.447, which exceeds the critical value for the null hypothesis (Ho). Since the t-value (3.447) > t-table (2.571), the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The study's findings demonstrate a distinction between the standing pointing throw and the squatting pointing throw, as the calculated t-value (3.447) > t-table (2.571). Conclusion. The athletes from the Petanque Hamzanwadi Club meticulously compared and analyzed the throwing techniques of standing pointing and squatting pointing to gain a deeper understanding of the differences between the two methods.